Spreading of cattle paramphistomatoses on the territory of Poltava region - Yevstafieva , V. O.; Khorolskyi , A. A. (Scientific Progress & Innovations, 2019)
The purpose of the article is to study the peculiarities of spreading cattle paramphistomatoses on the farms of Poltava region. Methods of research. Parasitological methods (coproscopic sedimentation and flotation, identification of the pathogens of trematodoses, nematodoses and protozoases); epizootological (determining the invasion prevalence, age dynamics) were used. The research results. It was established that paramphistomatoses are common invasions of cattle in the conditions of individual peasant farms in Poltava region, with the average invasion extensiveness of 41.27 %. In all 5 combinations of paramphistomatides with the causal agents of nematodozes (strongylatoses of the digestive organs, trichurosis) and protozoasis (eimeriosis), occurring in the form of two- (83.33 %) and three-component (16.67 %) associations, were established. The association of paramphistomatides and strongyles of the digestive system (40.00 %), and also paramphistomatides and trichurises (26.67 %) was most often registered. More rarely, the association was found between paramphistomatides and eimeria (16.66 %), paramphistomatides, trichurises and eumeria (10.00 %), paramphistomatides, strongyles of digestive organs and eimeria (6.67 %). Age dynamics of paramphistomatosis is characterized by increasing the indicators of invasion prevalence with the age of animals. Cows appeared to be the most infested, and the invasion prevalence reached 56.92 %. The young cattle under the age of one year turned out to be the least infested with the causal agents of paramphistomatosis, the invasion prevalence here was 17.39 %. The elements of scientific novelty. The determining of epizootological aspects of cattle paramphistomatoses in Poltava region has been conducted. The age dynamics of the invasion and peculiarities of the course of paramphistomatoses in the composition of the mixed invasions of animal digestive system has been established. Practical significance. The obtained results of the peculiarities of epizootology for cattle paramphistomatoses will enable to plan effectively preventive anti-parasitic treatments of animals and health-improving measures.